2016
DOI: 10.1556/0806.44.2016.028
|View full text |Cite
|
Sign up to set email alerts
|

Syringaldazine peroxidase stimulates lignification by enhancing polyamine catabolism in wheat during heat and drought stress

Abstract: Six wheat cultivars, namely PBW 343, PBW 550 (stress susceptible), PBW 621, PBW 175 (drought tolerant), C 306 and HD 2967 (heat tolerant), were used in this study to evaluate the effect of heat and drought stress on the activities of peroxidases (POXs), diamine oxidase (DAO), polyamine oxidase (PAO) and arginine decarboxylase (ADC) and ornithine decarboxylase (ODC) in relation to contents of polyamines (PAs), lipid peroxide and lignin. High temperature (HT) elevated activities of syringaldazine peroxidase (SPX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Based on our data, it seems that in response/adaptation to the sun, heat, and drought, both N. northiana and rafflesiana developed a self-protection strategy by increasing lignification to inhibit water loss from plant tissue 87 . Similar adaptation mechanisms have been shown for Norway spruce, Ctenanthe setosa , and wheat 88 – 90 .…”
Section: Discussionsupporting
confidence: 76%
“…Based on our data, it seems that in response/adaptation to the sun, heat, and drought, both N. northiana and rafflesiana developed a self-protection strategy by increasing lignification to inhibit water loss from plant tissue 87 . Similar adaptation mechanisms have been shown for Norway spruce, Ctenanthe setosa , and wheat 88 – 90 .…”
Section: Discussionsupporting
confidence: 76%
“…Importantly, under drought stress, the LACCASE2 gene was observed to be downregulated by miR397b so that lignin deposition can be accelerated as a survival strategy (Sharma et al, 2020). In wheat plants, lignin deposition was observed to be enhanced by SYRINGALDAZINE PEROXIDASE via speeding up the polyamine degradation process upon drought (Bala et al, 2016). In a study on maize plants, the lignin-based hydrogel was found to be promising to mitigate drought-related adversities by elevating water content, proline, phosphorus, and biomass and by reducing electrolyte leakage (Mazloom et al, 2020).…”
Section: Lignin In Drought Stressmentioning
confidence: 99%
“…Several studies across various species have demonstrated that water stress leads to a decrease in lignin content (Moura et al, 2010; Dos Santos et al, 2015; Van Der Weijde et al, 2017; Perrier et al, 2017; EL Hage et al, 2018), as well as in PCest when investigated (El Hage et al, 2018). Furthermore, although studies focusing on the isolated effect of heat stress are rarer, they suggest an influence of heat on the lignification process (Bala et al ., 2016). The synthesis of phenolic compounds represents a significant and irreversible investment of carbon and energy for the plant, subject to various regulatory levels.…”
Section: Discussionmentioning
confidence: 99%